P-143 Does Ustekinumab Affect Postoperative Outcomes in Patients Undergoing Abdominal Operations for Crohn's Disease?. (February 2017) - Lightner, Amy; Raffals, Laura; Pemberton, John; Edward, Loftus; Kane, Sunanda; Mathis, Kellie
Abstract : Background: Ustekinumab, a humanized monoclonal antibody to the p-40 subunit of interleukin 12 and 23, remains a study drug for patients with Crohn's disease (CD). Clinical trials are currently addressing the drug's efficacy and safety for the treatment of CD. No study to date has investigated postoperative complications among patients who received ustekinumab in the perioperative period. The potential impact of medical therapy is an important consideration in determining operative timing and the need for fecal diversion. We sought to determine the 30-day postoperative complication rate among patients who received ustekinumab within 12 weeks of an abdominal operation for CD. Methods: A retrospective chart review between January 2013 and April 2016 was conducted. Study patients were adults with CD who received ustekinumab within 12 weeks of an abdominal operation. Control cohorts were comprised of CD patients who underwent an operation and received either anti TNF-a biologic therapy or no biologic therapy. Data abstracted included patient demographics, concomitant immunosuppressive medications, operation performed, and 30 days postoperative complications. Univariate and multivariate analysis was performed to look for significant differences in the study and control cohorts. Results: Fifteen patients were included in the study group, 109 patients received no biologic therapy, and 105 received anti TNF therapy. Within the study group, 9 patients were female, and the median age was 34 years. Median duration of CD was 13 years, the most common disease location was terminal ileum (n = 7), and median number of prior abdominal operations was 4. No patients were actively smoking. Ten patients were also receiving steroids, and 3 immunomodulators. The most common indication for an operation was colitis (n = 6), and the operations performed were colectomy (n = 5), small bowel resection (n = 4), ileocectomy (n = 3), pouch excision (n = 2), and diverting loop ileostomy. The surgical site infection (SSI) rate was 27% (n = 4) compared to 10% in both control cohorts ( P = ns). The rate of return to the operating room (ROR) was 27% (n = 4), significantly higher than a rate of 4% and 9% in the control cohorts ( P < 0.01) On univariate analysis, patients on ustekinumab were significantly younger ( P < 0.05), more likely to be on concomitant steroids ( P < 0.001), less likely to be on an immunomodulator ( P < 0.002), more likely to have a diverting ostomy ( P < 0.01), a postoperative complication ( P < 0.03), and a return to the operating room ( P < 0.01) On multivariate analysis, after accounting for age, steroid use, and immunomodulator use, any postoperative complication remained significantly increased in the ustekinumab cohort ( P < 0.01). Conclusions: Among CD patients who underwent a major abdominal operation within 12 weeks of ustekinumab infusion, 27% experienced an SSI, clinically higher than the 10% SSI rate in the anti-TNF a cohort or no biologic therapy cohort. In addition, patients had a significantly higher ROR. While this investigation is preliminary and the study population small, complications need to be closely and prospectively tracked in patients on ustekinumab undergoing surgery.